Chk2 sustains PLK1 activity in mitosis to ensure proper chromosome segregation - Elizabeth M. Black; Carlos Andrés Ramírez Parrado; Isabelle Trier; Wenxue Li; Yoon Ki Joo; Jennifer Pichurin; Yansheng Liu; Lilian Kabeche (Nature Communications)
Abstract Polo-like kinase 1 (PLK1) protects against genome instability by ensuring timely and accurate mitotic cell division, and its activity is tightly regulated throughout the cell cycle. Although the pathways that initially activate PLK1 in G2 are well-characterized, the factors that directly regulate mitotic PLK1 remain poorly understood. Here, we identify that human PLK1 activity is sustained by the DNA damage response kinase Checkpoint kinase 2 (Chk2) in mitosis. Chk2 directly phosphorylates PLK1 T210, a residue on its T-loop whose phosphorylation is essential for full PLK1 kinase activity. Loss of Chk2-dependent PLK1 activity causes increased mitotic errors, including chromosome misalignment, chromosome missegregation, and cytokinetic defects. Moreover, Chk2 deficiency increases sensitivity to PLK1 inhibitors, suggesting that Chk2 status may be an informative biomarker for PLK1 inhibitor efficacy. This work demonstrates that Chk2 sustains mitotic PLK1 activity and protects genome stability through discrete functions in interphase DNA damage repair and mitotic chromosome segregation.